SEGURANÇA ALIMENTAR, PRODUÇÃO AGRÍCOLA FAMILIAR E ASSENTAMENTOS DE REFORMA AGRÁRIA NO MARANHÃO - Silva, José de Ribamar Sá (2007)
It s studied the family farming importance in the agrarian reform s settlements, which has the Maranhão state as its empiric base, in the contemporary context of building of the food and nutritional safety. It s established a vision of the contradiction between the productive forces development and the relations of production in capitalism, pointing out the fact that a big percentage of the world population still starve, in spite of the social capacity to produce food technically is very developed. It s argued that the Green Revolution has provided the agrarian modernization intrinsically concentrative, whose social effects become obvious in the rural poverty increasing. We see that, in Brazil, the current agrarian reform system hasn t been able to promote the solutions of the problems which affect the family farming. Emphasizing that, in the presence of the recent tendency to revalorize the rural zone as an area of production, housing and leisure, and with the emergency of the discussion about the food and nutritional safety, it s created an opportunity to the societies which are characterized by a strong social difference to promote structural reforms. In this context, it is defended the existence of the agrarian reform s settlements as a privileged locus to the family farming development, being this understood as the most efficient social form to produce food aiming at the guarantee food and nutritional safety to the whole society.